A Conceptual Framework for the Lean Research and Development - binti Mohd Hamel, Nabila; Owee Kowang, Tan; Chin Fei, Goh (International Journal of Engineering and Technology, 2018)
Both lean R&D soft practices success factor and lean R&D tools and techniques are the improvement strategies to reduce cost, increase speed and deliver superior quality in R&D organization. In order to achieve higher performance, an R&D organization needs to adopt both lean R&D soft practices success factor, and lean R&D tools and techniques. Therefore, the main objective of this paper is to review the relationship among lean R&D soft practices success factor, lean R&D tools and techniques, and R&D based organization performance. After an extensive review of literature, a new lean R&D model in R&D based organization is developed with an objective of developing a theoretical knowledge for R&D based organization in order to understand more systematically the relationship among lean R&D soft practices success factor, lean R&D tools and techniques, and R&D based organization performance. The proposed model examines the impact of lean R&D tools and techniques as the mediating effect between lean R&D soft practices success factor and R&D based organization which has not been evaluated earlier. The paper also includes a review to identify existing theoretical perspectives that could be considered as a basis for the creation of a new conceptual framework of lean R&D.